A Dynamic Model of Banking Efficiency, Stability, and Competition in Indonesia - Nur'aini, Dyah Tari; Damayanty, Prisila; Mubarok, Faizul (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The banking industry plays a vital role in Indonesia's economy, yet the dynamics among efficiency, stability, and competition levels often exhibit complex and not fully understood relationships. This study aims to analyze a dynamic model that describes the short- and long-term interactions between efficiency, stability, and competition in Indonesia's banking industry during the period 2015–2023. The research employs a quantitative approach using the Vector Error Correction Model (VECM) to examine the causal effects and the contribution of shocks among the variables. Secondary data were obtained from annual bank financial statements, OJK statistics, and Bank Indonesia publications. The findings indicate that competition positively affects efficiency, in line with the competition-efficiency hypothesis and quiet life hypothesis, but exhibits a nonlinear relationship with stability: increasing short-term risk but enhancing long-term stability, as described by the competition-stability hypothesis. Stability consistently improves efficiency and competition in both the short and long term, while the impact of efficiency on competition is more limited. The Impulse Response Function and Forecast Error Variance Decomposition analyzes also show that each variable initially dominates its own variability, with the contribution of other variables gradually increasing over the long term. These findings offer important implications for regulators and banking practitioners in formulating strategies to enhance competitiveness, improve efficiency, and maintain stability sustainably.